The Existence of Gender Equality in Leadership: A Perspective of Sa‘id Ramdhan al-Buthi - Ahmad, Ali; Ismail Birrur Rohman; Ahmad Fauzi (Syariah: Journal of Fiqh Studies, 2025)
Gender equality, especially concerning leadership, is a complex topic in Islam. Issues of feminism and women's emancipation are often considered taboo in Muslim communities in Pakistan. Traditional Muslim scholars, influenced by the cultural dimensions of Islam in their era, formulated laws regarding male supremacy over women in their writings. In contrast, in the modern era, contemporary Muslim scholars, such as Dr. Said Ramdhan al-Buthi, engaging with Western knowledge, have attempted to establish new paradigms regarding feminism, particularly concerning women's leadership, while remaining grounded in scriptural analysis. This study aims to describe al-Buthi's views on gender equality in women's leadership. Al-Buthi's perspective holds particular value in legitimizing feminism within Islam, as his arguments are strongly rooted in the Qur'an and Hadith. This study was qualitative and adopted a library-based research design. Data were collected from al-Buthi's writings and other relevant literature and analyzed using narrative synthesis and content analysis. The findings indicate that, in al-Buthi's view, women are granted access to leadership, albeit with certain limitations, which differs from the general prohibitions of traditional scholars. This finding suggests that socio-cultural aspects can influence scholars' decisions and simultaneously promote inclusivity in leadership.